Palivizumab: The Effects of Prophylactic Immunization on the Occurrence of Infections Caused by the Respiratory Syncytial Virus - Raguz, Marjana Jerkovic; Brzica, Jerko; Grgic, Ivana (Klinische Pädiatrie, 2017)
Aim The aim of this research is to analyze the characteristics of children immunized during immunization season, and their readmission to hospital due to infections of the respiratory tract in the period from 2008 to 2016.Method The retrospective cohort study included 101 children. The test group consists of infants who met the strict criteria for immunization. The national guidance was determined on the basis of earlier research and recommendations by the AAP. All the children who had been readmitted for hospitalization were quickly tested for RSV.Results Of this total, 47 children were preterm children (46.5%), 43 (42.5%) were children with CHD, and 11 (11%) exhibited other individual risk factors (gestational age 33–34 weeks, neurological disorders, respiratory anomalies, multi-organ anomalies). 25 (24%) patients of the immunized study population readmitted the ward due to respiratory infections. Of these, 50% were under the age of 6 months and were treated for less than a week on average. Upon readmission, a quick test to diagnose for RSV infections was conducted, which was negative for all of the previously immunized children.Conclusion Palivizumab represents an effective prevention to avoid RSV infections, that significantly contributes to mortality for children at risk, especially in developing countries.
Keywords: immunization; preterm infants; respiratory Syncytial virus; respiratory tract infections